Blended Learning in the Education System Of Uzbekistan - Toxta Ametovna Yuldasheva (Academia One Publishing, 2023)
The article talks about the fact that support for the activities of blended education is a topical issue in the current globalization period, as well as aspects of blended education that are superior to traditional education.
Keywords: blended learning; Remote education; informatization; information Technology